2010
DOI: 10.1007/s00268-010-0400-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Lymph Node Metastasis in Patients Undergoing Partial Hepatectomy for Hepatocellular Carcinoma

Abstract: Lymph node metastasis in patients with HCC is closely related to a lower survival rate. Regional lymph node dissection should always be performed to determine the precise stage of the disease. Hepatic resection with regional lymphadenectomy is a safe procedure in patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 27 publications
3
52
0
5
Order By: Relevance
“…Lymph node metastases (LNM), which contribute to the risk of cancer death (3), are found in approximately 7.45% of HCC patients (4). We have reported that LNM in HCC is sensitive to external beam radiotherapy (5), but the quality of life and survival of patients who undergo this procedure remains unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node metastases (LNM), which contribute to the risk of cancer death (3), are found in approximately 7.45% of HCC patients (4). We have reported that LNM in HCC is sensitive to external beam radiotherapy (5), but the quality of life and survival of patients who undergo this procedure remains unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Portal vein involvement, lymph node metastasis and extrahepatic metastasis had been found to be poor prognostic variables in multiple studies [22][23][24][25][26]. Portal venous thrombosis can lead to complications of portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of regional (hilar or perihepatic) lymph node metastases remains incompletely defined; although the presence of such nodal metastases seems to be an ominous sign, the prevalence of nodal metastases seems to be low. [9][10][11][12] Although the development of extrahepatic metastases portends a poor outcome, the preneoplastic nature of chronic liver diseases often makes the risk of intrahepatic recurrence higher than the risk of distant metastasis. 13,14 One prognostic variable that has consistently been shown to indicate a higher likelihood of recurrent disease after resection or transplantation is vascular invasion by tumor.…”
Section: Prognostic Variablesmentioning
confidence: 99%